15 Predictors of right ventricular remodelling in reperfused inferior myocardial infarctions: cmr voxel feature tracking based feasibility study. (26th April 2015) - Garg, P; Kidambi, A; Ripley, DP; Dobson, LE; Swoboda, PP; Musa, TA; McDiarmid, AK; Erhayiem, B; Haaf, P; Greenwood, JP; Plein, S
Abstract : Background: RV function after STEMI has important prognostic implications. However, changes in RV function over time after inferior-STEMI and the incidence of RV remodelling remain unclear. We aimed to investigate which parameters of RV function after inferior-STEMI influence RV remodelling at 3 months. Methods: Twenty-one patients underwent CMR at 3T (Achieva CV, Philips Healthcare, Best, The Netherlands) within 3-days and 90-days following reperfused inferior/posterior STEMI. The CMR protocol included: cines and LGE imaging (0.1 mmol/kg gadolinium DTPA). Infarct location was determined from LGE images. Indexed RV end-diastolic volume (RVEDVi), end-systolic volume (RVESVi) and ejection fraction were derived from the short-axis stack cines for day-3 and day-90 scans. Offline strain analysis was performed for day-3 scans by voxel feature tracking (FT) for the RV and RA in the 4-chamber cines using commercially available software (cvi42 v5.1, Circle Cardiovascular Imaging Inc., Calgary, Canada). Results: Mean age of our population was 57 ± 12 years-old. 86% patients were male. RV EF improved significantly from day-3 scan to day-90 scans (40 ± 12.6% vs. 49 ± 10.9%, p < 0.001). Day-3 RV EF demonstrated correlation to RV PLS (p = 0.03), RV PRS (p = 0.03) and RA TTP LSR (0.018). On multivariate stepwise analysis, RV PLS showed the strongest correlation (R=0.44; p = 0.04). Day-90 RV EF was most strongly correlated to TTP of LSR of RA (R=0.48, p = 0.048). Relative change in RV EF was also correlated to RV PLS (p = 0.03). Conclusion: Voxel FT derived RV functional parameters, mainly PLS, correlates well with Day 3 RV EF and with relative change of RV EF at day-90. Interestingly, day-90 RV EF showed the strongest correlation to time to peak longitudinal strain rate (TTP LSR) of the RA. This may be because TTP SR parameters reflect mechanical dyssynchrony after the acute ischaemic event. This concept needs further clarification in larger studies.